Thinking about Christian Life in the Turmoil Times of the Middle East - Insights and Reflections from East and West - Tamcke, Martin (Universitätsverlag Göttingen, 2020)
"Studies in the Middle East" is a one-year programme at the Near East School of Theology in Beirut (NEST). In honour of its 20th anniversary, academics and teachers from the NEST and from Germany met at Georg-August University in Göttingen and in the nearby Coptic Orthodox Monastery in Höxter-Brenkhausen to discuss the current situation in the Middle East and possible ways to initiate a spiritual new beginning in this crisis and war-ridden region. The present volume offers various contributions that were made on the subject.